Photooxidation Coupled Kabachnik–Fields and Bigenelli reactions for Direct Conversion of Benzyl alcohols to α-Amino Phosphonates and Dihydropyrimidones. - Gazunfor Ali; Nisar A Dangroo; Shabnam Raheem; Tahira Naqvi; Tabassum Ara; Masood Ahmad Rizvi (Acta Chimica Slovenica, 2020)
A tandem one-pot solvent free approach for the direct conversion of benzyl alcohols to α-amino phosphonates and dihydropyrimidones is reported. The method relies on a metal free photo-oxidation of benzyl alcohols to benzaldehydes under UV irradiation using ammonium perchlorate followed by Kabachnik–Fields and Biginelli reactions. The reaction conditions are moderate and metal free with good substrate scope. The control experiments were performed to investigate the role of the ammonium perchlorate and molecular oxygen as oxidants. The quenching experiments in the presence of TEMPO and other radical quenchers suggest radical based mechanism.